Nursing therapy in the transition from blind women's maternity (Research, Society and Development, 2020)
This study aimed to discuss the transition process of motherhood from the perspective of blind women, in the light of the Transition Theory. It is a qualitative, descriptive research, developed in the countryside of the state of Bahia. Intentional sample composed of 11 women who were already blind when they became mothers. The narratives were collected through an open interview, using the Life Narrative approach. Data analysis took place in the light of the theoretical framework of the Transitions Theory. From the life narratives, it was possible to identify, at which times nursing can act to meet the needs of these women and in which situations the nursing care is essential for the transition process to blind women's motherhood. The direction of a more accurate look at women with disabilities in the communities served and health services is increasingly necessary.